Distinct element method analysis and field experiment of soil resistance applied on the subsoiler - Bo, Li; Fanyi, Liu; Junying, Mu; Jun, Chen; Wenting, Han (International Journal of Agricultural and Biological Engineering, 2014)
Since the design of the subsoiler is a complex work, the interaction between the subsoiler and soil was investigated by using Distinct Element Method (DEM) in this study. Based on the traditional discrete element theory, the 3D model of soil particles and the subsoiler were established after considering the liquid bridge force between soil particles. The operating resistance curves of the subsoiler were achieved after the DEM simulation at a speed of 1 m/s, and three depths of 180 mm, 220 mm and 260 mm, respectively. The simulation curves agreed well with the field experimental results based on relative errors of 2.96%, 14.95% and 7.15%, respectively, at three depths. All these data proved that it was feasible and favorable to analyze the performance of the subsoiler by using the DEM and it is of important significance for studying and further optimizing the structure of the subsoiler.